If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + 2) + -1(-5) = 8x + -13 Reorder the terms: (2 + 5x) + -1(-5) = 8x + -13 Remove parenthesis around (2 + 5x) 2 + 5x + -1(-5) = 8x + -13 Multiply -1 * -5 2 + 5x + 5 = 8x + -13 Reorder the terms: 2 + 5 + 5x = 8x + -13 Combine like terms: 2 + 5 = 7 7 + 5x = 8x + -13 Reorder the terms: 7 + 5x = -13 + 8x Solving 7 + 5x = -13 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 7 + 5x + -8x = -13 + 8x + -8x Combine like terms: 5x + -8x = -3x 7 + -3x = -13 + 8x + -8x Combine like terms: 8x + -8x = 0 7 + -3x = -13 + 0 7 + -3x = -13 Add '-7' to each side of the equation. 7 + -7 + -3x = -13 + -7 Combine like terms: 7 + -7 = 0 0 + -3x = -13 + -7 -3x = -13 + -7 Combine like terms: -13 + -7 = -20 -3x = -20 Divide each side by '-3'. x = 6.666666667 Simplifying x = 6.666666667
| ((x^2)-8x-19)=0 | | (-6t^3)(-5t)= | | 3(x+6)=6(x-8) | | 10-1/2x=2 | | (-1.9)(-9.1)= | | (-1.9)x(-9.1)= | | p(t)=690.4t+11634 | | -5(9x+6)=-6x | | log[4](x+63)+log[4](x+15)=5 | | 2(3y-1)=12 | | 23=-4x | | (-8p^2-9p+9)+(6p-8)= | | 5x-15y=135solvey | | (2x^2-3x+7)-(1-12x)= | | tan(30+x)=2tan(60-x) | | 9k-(6+k)=-(2k+6) | | 6x+9-3x=19 | | 8p+18=-70 | | 6(x-5)-3x=-9 | | (7s^2+6s-3)-(-6s-1)= | | 6(y-5)+7(y+3)=95 | | 4x^2-98x+180=0 | | 10(1+3xb)=-20 | | (8v^3+8v^2+6v+6)-(6v+3)= | | -1/3-1/5x-3/4 | | (5v^2+3v+8)+(-2v^2+2v)= | | 4(-3x-4)=-17x-5 | | ((x^2)+4x-3128)=0 | | -10=y+(-9) | | 5t-5=5 | | 7x-14/49 | | 8=x+(-2) |